Comparison of Open versus Closed Reduction and Intramedullary Nailing in cases of Closed Tibial Shaft Fractures - Abdul Rasheed Napar (Journal of Rawalpindi Medical College, 2021)
Objective: To compare the frequency of various post-operative complications in open versus closed reduction and intramedullary nailing in cases of closed tibial shaft fractures. Study Design: Comparative prospective study. Settings: Orthopedic Surgery Department, Khairpur Medical College, Khairpur Mirs. Study Duration: 1st February 2019 till 30 June 2020. Materials and Methods: Hundred and seventy patients selected for this study were divided into Group C (Closed percutaneous) and group O (Open). A closed percutaneous procedure was performed through a small stab incision. Reduction and stabilization of fracture were accomplished with large forceps and manual traction. Open reduction was achieved through an adequate incision for exposure and then directly reducing the fracture. The reduction was maintained with the help of clamps. Follow-ups were carried out to look for surgical site infection, deep infection, mal-union, delayed union and nonunion, iatrogenic nerve injury. Results: Surgical site infection was seen in 5 (5.88%) patients in group C and 9 (10.58%) in group O (p-value=0.404). Deep infection was seen in 3 (3.53%) patients in group C and 7 (8.34%) in group O (p-value=0.329). Mal-union was seen in 4 (4.71%) and 2 (2.35%) patients in group C and O respectively (p-value=0.682). Delayed union was seen in 4 (4.71%) and 3 (3.53%) patients in group C and O respectively (p-value=1.0). Non-union was seen in 2 (2.35%) and 1 (1.18%) patients in group C and O respectively (p-value=1.0). Iatrogenic nerve injury was not seen in either group. Conclusion: It is concluded in our study that there is no significant difference in the rate of post-operative complications in open versus closed reduction and intramedullary nailing in cases of closed tibial shaft fractures.